Evaluating the Effect of Microcredit on Rural Livelihoods: A Case Study of Farming Households in Southwest Nigeria - Ilesanmi, Julius Olumide; Bello, Temitope Olanrewaju; Oladoyin, Olanrewaju Peter; Akinbola, Adeyose Emmanuel (International Journal of Economic, Finance and Business Statistics, 2024)
Access to credit is an important thing in improving the livelihoods of rural families in developing international locations, enabling them to triumph over monetary barriers and spend money on productive activities. This observation evaluates the impact of microcredit on the livelihoods of rural farming households in Southwest Nigeria, specializing in assets of credit and elements influencing credit access. Descriptive facts and multinomial logistic regression were used to analyse the information. Results show that informal credit sources, such as family and friends, are predominantly utilized by 97.5% of respondents, while only 8.3% accessed microfinance banks. The average credit amount received was ₦167,000, with limited utilization primarily due to constraints like market access and lack of technical knowledge. Agricultural activities such as crop production and livestock farming dominate rural livelihoods, suggesting that microcredit plays a crucial role in improving productivity. However, findings indicate that higher education levels, income, and household size significantly influence the likelihood of accessing formal and informal credit. The study concludes that microcredit has the potential to improve rural livelihoods, but formal credit systems must be expanded to reduce reliance on costly informal sources and enhance the overall welfare of rural households.